New record of Coomansus venezolanus (Loof, 1964) Jairajpuri & Khan, 1977 (Mononchida: Mononchidae) for Vietnam with first description of a male - Thanh Tam, Vu Thi (Academia Journal of Biology, 2016)
Coomansus venezolanus (Loof, 1964) Jairajpuri & Khan, 1977 from Cao Loc, Lang Son province is described and illustrated and represents a new record for Vietnam. The species is characterized by its body size, 1.9-2.1 mm long, a strongly sclerotized buccal cavity with apex of dorsal tooth situated at 26-30% of buccal cavity length from anterior end and vulva at 60-64% of body length from anterior end. A single male specimen is reported for the first time and is characterized by having fifteen spaced ventromedian precloacal supplements, a 74 mm long spicule; well developed lateral accessory pieces, 12.5 mm long and a weakly developed gubernaculum, 11.4 mm long. Measurements and description of the Vietnamese female specimens fit well the holotype, except for a slightly slenderer body (a = 27-31 vs 21) and shorter tail (c = 20-28 vs 18); they also agree with the specimen from Himachal Pradesh, India apart from a slightly shorter tail and a slightly stouter body.